2017
DOI: 10.1016/j.jmaa.2016.11.041
|View full text |Cite
|
Sign up to set email alerts
|

Harmonic reflection in quasicircles and well-posedness of a Riemann–Hilbert problem on quasidisks

Abstract: A complex harmonic function of finite Dirichlet energy on a Jordan domain has boundary values in a certain conformally invariant sense, by a construction of H. Osborn. We call the set of such boundary values the Douglas-Osborn space. One may then attempt to solve the Dirichlet problem on the complement for these boundary values. This defines a reflection of harmonic functions. We show that quasicircles are precisely those Jordan curves for which this reflection is defined and bounded.We then use a limiting Cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 13 publications
0
28
0
Order By: Relevance
“…The operators P (Ω ± ) were shown to be well-defined maps which are bounded with respect to the Dirichlet semi-norm (1.3). It was also shown in [19] that the Faber operator is an isomorphism precisely for quasicircles. This remarkable result is originally due to Y. Shen [21], with a somewhat different formulation of the operator; closely related results for convergence of Faber series on quasidisks were obtained by A. Ç avuş [3].…”
Section: Grunsky Map For Multiply-connected Domainsmentioning
confidence: 91%
“…The operators P (Ω ± ) were shown to be well-defined maps which are bounded with respect to the Dirichlet semi-norm (1.3). It was also shown in [19] that the Faber operator is an isomorphism precisely for quasicircles. This remarkable result is originally due to Y. Shen [21], with a somewhat different formulation of the operator; closely related results for convergence of Faber series on quasidisks were obtained by A. Ç avuş [3].…”
Section: Grunsky Map For Multiply-connected Domainsmentioning
confidence: 91%
“…In the case when Γ is a Jordan curve separating the Riemann sphere into two components, the authors showed that the transmission exists and is bounded if and only if Γ is a quasicircle [28]. Our proof here of the general case uses sewing techniques for Riemann surfaces.…”
Section: Introductionmentioning
confidence: 93%
“…They also disproved a conjecture of Anderson that the Faber operator is a bounded isomorphism of Besov spaces B p for general Jordan curves. The formulation of Schippers and Staubach as a map between Dirichlet spaces for general quasicircles (in terms of the composition operator and Cauchy-type projection) required the jump formula on quasicircles as well as the existence of a bounded reflection of Dirichlet-bounded harmonic functions, obtained in [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear whether H + (Γ) and H − (Γ) are the same in general. However, on quasidisks we have by a result in[17, Theorem 2.14] thatH + (Γ) = H − (Γ)in the following sense. Fix conformal maps f : D + → Ω + and g : D − → Ω − .…”
mentioning
confidence: 99%
See 1 more Smart Citation